Chinese FDI and Zambian Development: A Critical Evaluation of the its Relevance through key Socio-Economic and Political Indicators - Dunkin, Cameron (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2012.